On the Impulsive Synchronization Control for a Class of Chaotic Systems - Bo Wang; Peng Shi; Xiucheng Dong (Discrete Dynamics in Nature and Society)
The problem on chaos synchronization for a class of chaotic system is addressed. Based on impulsive control theory and by constructing a novel Lyapunov functional, new impulsive synchronization strategies are presented and possess more practical application value. Finally some typical numerical simulation examples are included to demonstrate the effectiveness of the theoretical results.